2019
DOI: 10.1007/s12298-019-00718-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of colchicine induced tetraploidy on morphology, cytology, essential oil composition, gene expression and antioxidant activity of Citrus limon (L.) Osbeck

Abstract: Citrus limon (L.) Osbeck cultivated all over the world is a valuable source of aromatic essential oil. To develop tetraploids of C. limon, four different concentration of colchicine (0.025, 0.05, 0.1 and 0.2%; w/v) and three varied exposure time (12, 24 and 48 h) were employed. The ploidy level of diploids (2n = 2x = 18) and tetraploids (2n = 4x = 36) were determined by direct chromosome count and confirmed by flow cytometric analyses. Successful result with maximum tetraploidy frequency was observed in plantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…1 -2). Polyploidy is defined as the presence of more than two complete chromosome sets in a cell nucleus and is considered to be responsible for plant evolution and diversification [16]. Polyploids induced by colchicine may retain a small number of undetected chimeric cells even after regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…1 -2). Polyploidy is defined as the presence of more than two complete chromosome sets in a cell nucleus and is considered to be responsible for plant evolution and diversification [16]. Polyploids induced by colchicine may retain a small number of undetected chimeric cells even after regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…Although 16 homologue miRNAs were found in all 2x and 4x, two of them (miR482 and miR2916) significantly changed their expression, being either induced or repressed in 4x vs. 2x. MiR482 is known to be active in response to the inoculum of viruses, Verticillium dahliae , soybean cyst nematodes, and Ralstonia solanacearum [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. In particular, it is a negative regulator of tolerance to pathogens by targeting conserved sequences encoding the P-loop of NBS–LRR resistance proteins.…”
Section: Discussionmentioning
confidence: 99%
“…As far as miR5538 is concerned, we found that one of its target genes is protein-S-isoprenylcysteine O-methyltransferase , which is involved in the terpenoid backbone biosynthesis. The enzyme catalyzes the post-translational methylation of isoprenylated C-terminal cysteine residues [ 48 ]. This is particularly interesting since it has been long recognized that polyploidization can change the quality and quantity of secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
“… Colchicine; 0.6%; 24 h Increase in total anthocyanin (9.1%) Soaking in colchicine soln. Colchicine; 0.6%; 24 h Increase in total phenolic (NM) Citrus limon (L.) Osbeck MS + colchicine; 25 ± 2 °C; 16 h PP; 50–60 μmol/m 2 /s LI Seed with radicle Colchicine; 0.025%; 24 h Diploid➔tetraploid (2n=4x=36) Increase in essential oil and limonene (7%) [ 58 ] Eucalyptus polybractea RT Baker Solid medium M1 + colchicine; Dark; 25 °C; shaking at 40 rpm Shoot tip Colchicine; 0.5%; 4 d Diploid➔tetraploid (2n=4x=44) Increase in essential oil (3%) [ 59 ] Plantago psyllium Colchicine treatment (dissolved in 2% DMSO) Terminal bud Colchicine; 0.5%; 24 h Diploid➔tetraploid (2n=4x=24) Increase in carotenoid (1.5-fold) [ 60 ] NM Trifluralin; 22.5%; 72 h Increase in carotenoid (1.54-fold) Plantago ovata Soaking in colchicine soln. Terminal bud Colchicine; 0.3%; 24 h Trifluralin; 22.5%; 72 h Diploid➔tetraploid (2n=4x=16) Increase in carotenoid content (approx.…”
Section: Introductionmentioning
confidence: 99%